The Sumedang Larang Royal Waqf: Legal Perspective - Rafiqi, Yusep; Suryanto, Asep; Athoillah, Mohamad Anton (AHKAM : Jurnal Ilmu Syariah, 2023)
The governance of royal waqf has not been addressed in Indonesian waqf laws and regulations. It also implies that the potential benefits of the waqf have not been sufficiently explored. Actually, the royal waqf has significantly contributed to the field of waqf by preserving cultural heritage and wisdom. This article demonstrates, through the testamentary waqf of Prince Aria Soeria Atmadja (Regent of Sumedang, 1883-1919 AD), the importance of waqf status and the insertion of royal relics into waqf legislation in Indonesia to ensure their perpetuity and benefit future generations. The research employs a normative empirical methodology, wherein the historical context, laws about waqf, and waqf legislation are substantiated through observations, elucidations, and discoveries concerning the cultural and customary aspects of waqf governance. This research on royal waqf can at least suggest two things: the inclusion of a discrete article in Indonesian waqf legislation addressing royal waqf and the significance of royal family relics as waqf. Abstrak: Wakaf keluarga kerajaan berikut tata kelolanya belum terakomodasikan dalam peraturan perundang-undangan wakaf di Indonesia. Hal ini berimplikasi pada nilai-nilai yang terkandung di dalam wakaf tersebut tidak tereksplorasi dengan baik. Padahal, wakaf keluarga kerajaan ini memiliki sumbangsih yang cukup besar dalam wakaf, di antaranya pelestarian kearifan dan cagar budaya. Dengan mengambil contoh wakaf Pangeran Aria Soeria Atmadja (Bupati Sumedang, 1883-1919 M), artikel ini menunjukkan tentang betapa pentingnya benda-benda peninggalan kerajaan berstatus wakaf dan diakomodasi dalam perundang-undangan wakaf di Indonesia sehingga keabadian dan kebermanfaatannya dapat dirasakan oleh generasi yang akan datang. Ini adalah penelitian normatif empiris di mana latar belakang sejarah, hukum yang berkaitan dengan wakaf dan perundang-undangan wakaf dikonfirmasi] melalui observasi, klarifikasi, dan temuan tentang budaya dan adat istiadat yang berkaitan dengan tata kelola wakaf. Penelitian wakaf kerajaan ini setidaknya dapat merekomendasikan dua hal: pentingnya benda-benda peninggalan keluarga kerajaan sebagai wakaf dan memasukkan wakaf kerajaan dalam satu pasal tersendiri dalam peraturan perundang-undangan wakaf di Indonesia.